Evaluating a health video on diabetic retinopathy. (9th February 2016) - Meyer, Joos; Johnson, Karim; Bowyer, Joshua; Muir, Josephine; Turner, Angus
Abstract : Issue addressed: Indigenous Australians are 14 times more likely than non‐Indigenous Australians to develop diabetic retinopathy (DR). Blindness can be prevented in 98% of cases if DR is identified and treated early. While the National Health and Medical Research Council recommend annual screening for Indigenous Australians, screening attendance rates remain low. The objective of this study was to evaluate whether a targeted health promotion intervention improved patient compliance and screening rates. Methods: Bad Sugars, Bad Eyes – a culturally appropriate video targeting DR awareness and the importance of screening among Indigenous Australians – was developed at the Lions Eye Institute, Western Australia. The study used a patient questionnaire pre and post viewing of the video, as well as semi‐structured interviews with Aboriginal Health Workers, to explore the influence the resource had on patient knowledge and attitudes. Eighty‐four participants, currently involved in DR screening programs, were recruited from Aboriginal Medical Services (AMS) and Aboriginal Community Controlled Health Services (ACCHS). Results: The video was found to increase patient knowledge about key DR issues as well as alter patient attitudes identified as potential barriers to screening. The areas most affected by the video resource were knowledge of recommended screening intervals, the severity of potential visual complications if DR is left undiagnosed and untreated and that screening is needed even when asymptomatic. Aboriginal Health Workers positively evaluated the video, all rating it as 'very' culturally appropriate, understandable and relatable. Conclusion: The findings of this study suggest that Indigenous DR screening attendance rates could be increased through the expanded use of this video. So what?: Indigenous DR screening attendance rates remain low, despite annual recommendations by the National Health and Medical Research Council. This gap needs to be addressed. Abstract : Annual screening for diabetic eye disease is recommended for Indigenous Australians, as blindness can be prevented in 98% of cases if the disease is identified and treated early. This study evaluated the impact of a health promotional video on patient compliance and screening rates, with findings demonstrating an increase in knowledge and alterations in attitudes about key disease issues. This study suggests that screening rates could be increased through expanded use of this video.